2018
DOI: 10.3928/24748307-20171227-01
|View full text |Cite
|
Sign up to set email alerts
|

A Linguistic Analysis of Health Literacy Demands of Chronic Kidney Disease Patient Education Materials

Abstract: Background: Instruments to assess the quality and comprehensibility of printed patient education materials may lack proper consideration of how readers derive meaning from text. The Evaluative Linguistic Framework (ELF) considers how factors that influence readers' expectations about health care texts also affect their ability to understand them. The ELF has demonstrated value in improving the quality of patient materials about medication, consent, and self-reported questionnaires, but has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The aim of the information sheets was not clear. Attempting to accommodate multiple aims and purposes is known to impact upon the clear and factual nature the information sheets (Morony et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the information sheets was not clear. Attempting to accommodate multiple aims and purposes is known to impact upon the clear and factual nature the information sheets (Morony et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They are also entitled to know about the side effects that may result from this involuntary treatment. Other studies using the ELF have found that rhetorical functions should only be used in information sheets to increase clarity and reduce ambiguity of statements and to make information sheets actionable (Morony et al., 2018). It is a fundamental expectation that the language of a patient information sheet is neutral and accurate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations